Single crystal silicon wafer polishing by pretreating pad adsorbing SiO2 grains and abrasive-free slurries. (April 2022) - Bu, Zhengzheng; Niu, Fengli; Chen, Jiapeng; Jiang, Zhenlin; Wang, Wenjun; Wang, Xuehan; Wang, Hanqiang; Zhang, Zefang; Zhu, Yongwei; Sun, Tao
Abstract: Single crystal silicon wafers are widely applied in the field of Integrated Circuits (ICs). However, in order to pursue high surface quality and efficient material removal rate (MRR) on polishing single crystal silicon, a large amount of abrasives is consumed, which increases the processing cost and burdens the environment on discharge. A novel abrasive-free method of polishing single crystal silicon wafers was proposed and explored to solve the above problems. A polishing pad pretreated by colloidal silica was employed. The MRRs of the polished silicon wafers with potassium carbonate, potassium silicate and potassium hydroxide slurries before and after pretreating pads were measured and compared. The polishing pad pretreated by colloidal silica can improve the processing efficiency, stability and quality of single crystal silicon wafers in the abrasive-free slurries containing potassium carbonate, potassium hydroxide or potassium silicate. The outstanding MRR of silicon wafer was obtained using abrasive-free slurries containing potassium carbonate and potassium silicate. The material removal mechanisms of polishing single crystal silicon wafers with pretreating pad adsorbing SiO2 grains and abrasive-free slurries were investigated by XPS analysis of silicon wafer surfaces and EDS and SEM analysis of the pad surfaces. Highlights: An abrasive-free slurry polishing method for silicon wafers with reduced processing cost was developed. The silica grains adsorbed on the pad during the polishing process can be regarded as a fixed abrasive pad. The removal mechanism of silicon wafers polished by the pretreating pad adsorbing SiO2 grains is discussed. A synergetic action between SiO2 grains adsorbed the pad and abrasive-free slurry is pivotal in stable silicon polishing.